Measuring powder flowability with a modified Warren Spring cohesion tester - Mohammed, S.A.; Abdullah, E.C.; Geldart, D.; Abdul Raman, Abdul Aziz (2011)
The measurement of powder flowability is a major concern for most industrial processes that deal with the handling of bulk solids as raw materials, intermediates, or products. The development of devices that measure the flowability of non-aerated powders has not progressed as rapidly as might have been hoped since most research activities have been based on various types of shear testers intended to aid the design of hoppers. A new flowability indicator named as weighted cohesion (WS) is established using newly improved version of direct cohesion texture. A cornerstone of the proposed technique is that the procedure is automated, using a digital Warren Spring tester called Warren Spring-University of Malaya cohesion tester (WSUMCT), thus making results operator-insensitive. Besides being a practical tool to diagnose the cohesion of experimental powders, the ratio between measured cohesion (using WSUMCT) and aerated density (using Hosokawa PT-S) provides us with a powerful technique to research fundamental particle internal cohesion forces directly and use these data to indicate the flowability. In this work, a series of fine (9.4 mu m) and coarse (60 mu m) porous silica gel particle mixtures, and mixtures of fine (28 mu m) and coarse (72 mu m) glass ballotini as well, were used as test powders. The results from these tests agree well with relative flowability determined on our newly driven indicator using WSUMCT. The validation of aerated weighted cohesion (WSA) as a flowability indicator was authenticated by comparing the conducted parameter with established measured Hausner ratio (HR) and angle of repose (AoR). (C) 2011 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights reserved.